Ocular Adverse Effects in Atopic Dermatitis Patients Treated With Dupilumab: A Bibliometric Analysis - Jia, Qian-Nan; Qiao, Ju; Fang, Kai; Zeng, Yue-Ping (Frontiers in Medicine, 2022)
Background Atopic dermatitis (AD) is one of the most common chronic inflammatory skin disorders. Dupilumab, the first targeted biological drug approved for the treatment of AD, has been widely used, along with increasing ocular adverse effects (AEs). Objective To perform a bibliometric analysis of all the qualified literature involving ocular AEs during the treatment of AD with dupilumab. Methods Relevant literature were extracted from the Web of Science database and screened by researchers. The bibliographic analysis was performed using VOSviewer. Results A total of 138 articles were enrolled in this study. The first study was published in 2016 by Oregon Health and Science University from the USA. The majority of publications were published in the past three years. British Journal of Dermatology published the highest number of articles. The USA was the country with the most publications. Sanofi (France) and Regeneron Pharmaceuticals (USA) were the leading organizations with most contributions. Conjunctivitis was the most common ocular AE. The management of AD will continue to be the research hotspot and development trend in this area. The milestone research is the first article “Two Phase 3 Trials of Dupilumab versus Placebo in Atopic Dermatitis” published in New England Journal of Medicine. Most of the top 10 papers were mainly randomized, placebo-controlled phase 2 and phase 3 clinical trials and real-life large cohort studies. Conclusions This study may help better understand ocular AEs in the dupilumab treatment of AD, and grasp the research trends and most influential topics in this field.